Evaluation of the Impact of Educational Robotics on School Engagement: Educators' Perspectives - Ribeiro, Carlos Eduardo; Palácios, Rodrigo H. Cunha; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This study explores the impact of educational robotics on student engagement in a nonrormal learning environment, specifically within a non-governmental organization serving socioeconomically vulnerable children aged 7 to 13. Utilizing action research methodology, the study was conducted through a series of weekly workshops focused on unplugged computing and robotics activities. Data were collected using questionnaires completed by six teachers, who provided information on the academic and behavioral changes observed in 12 participating students. The findings reveal a positive impact on student engagement, problem solving skills, and intrinsic motivation, as well as improvements in classroom behavior and academic performance. Qualitative analysis highlights specific examples of improved student autonomy, responsibility, and collaboration as a result of the program. The study highlights the importance of integrating unppluged activies into nonformal educational practices as a means to improve engagement and provide access to learning opportunities for underserved communities.